Multiple-use water services to advance the millennium development goals - van Koppen, Barbara; Moriarty, P.; Boelee, Eline (International Water Management Institute, 2006)
This research report presents the findings of the first phase of the action-research project "Models for implementing multiple-use water supply systems for enhanced land and water productivity, rural livelihoods and gender equity." Multipleuse water services, or "mus" in short, is a participatory, integrated and poverty-reduction focused approach in poor rural and peri-urban areas, which takes people's multiple water needs as a starting point for providing integrated services, moving beyond the conventional sectoral barriers of the domestic and productive sectors.